Prognostic value of lymphocyte to monocyte ratio in patients with esophageal cancer: a systematic review and meta-analysis - Han, Yongqi; Zheng, Song; Chen, Yijing (Frontiers in Oncology, 2024)
ObjectivesTo report the largest systematic review and meta-analysis to evaluate prognostic value of lymphocyte to monocyte ratio (LMR) in patients with esophageal cancer.MethodsWe conducted a systematic literature retrieval via PubMed, Embase, Web of Science, and Cochrane until December, 2023 for studies which evaluated the prognostic value of LMR in patients with esophageal cancer. Outcomes measured were overall survival (OS), disease-free survival (DFS), relapse-free survival (RFS), and progression-free survival (PFS).Results11 studies including 3,377 patients with esophageal cancer were included for meta-analysis. Meta-analysis demonstrated that OS (HR: 1.65; 95% CI: 1.19, 2.31; P = 0.003) and DFS (HR: 1.48; 95% CI: 1.09, 2.01; P = 0.01) were significantly shorter in the low LMR group compared with the high LMR group. In addition, meta-analysis revealed a similar PFS (HR: 1.58; 95% CI: 1.00, 2.51; P = 0.05) and RFS (HR: 1.17; 95% CI: 0.93, 1.46; P = 0.18) in the two groups. Subgroup analysis found that the predictive value of LMR for OS remained significant in resectable and unresectable esophageal cancers, and in studies with follow-up ≥24 months and < 24 months. Subgroup analysis based on treatment methods found that the prognostic value of LMR was significant for both patients who received PD-1/PD-L1 inhibitors and those who did not receive PD-1/PD-L1 inhibitors. However, subgroup analysis based on LMR threshold found that the significance remained in studies with LMR threshold<3.5 (HR: 2.09; 95% CI: 1.13, 3.87; P = 0.02) but disappeared in studies with LMR threshold ≥ 3.5 (HR: 1.39; 95% CI: 0.93, 2.07; P = 0.11).ConclusionsLow LMR is associated with poor prognosis in patients with esophageal cancer. Due to the simple availability and low cost of routine blood tests in clinical practice, LMR can be widely used to assess prognosis and construct risk prediction models for patients with esophageal cancer.Systematic review registrationPROSPERO, identifier CRD42024509796.